Descriptive Study: Level of Communities Knowledge And Perception About Tuberculosis (TB) in Denpasar, Bali - Ni Putu Ayu Widiasari; Ida Ayu Jasminarti Dwi Kusumawardani; Ida Bagus Ngurah Rai (Indonesian Society of Respirology (ISR), 2020)
Background: Success rate of Indonesia Tuberculosis (TB) treatment did not evenly distribute to every province in 2016, although various program had been carried out by Indonesia Government. Bali’s Case Notification Rate (CNR) and Success Rate (SR) of TB also did not reach target in 2017. Successful control of TB can be influenced by community’s level of knowledge and perception about TB. Our research objective was to know communities level of knowledge and perception about TB in Denpasar, Bali. Method: This was cross-sectional research. Our sample was Denpasar communities who visited Puputan Renon Field Car Free Day (CFD) at 25 March 2018. Sample was chosen by consecutive sampling. Results: Our research result was almost (62%) of respondent had poor knowledge about TB and 67% respondent had right perception about TB. Conclusion: We can conclude that Denpasar communities had poor level of knowledge and good perception about TB.